KONTRIBUSI USAHATANI BAWANG DAUN TERHADAP PENDAPATAN KELUARGA DI DESA PALELON KECAMATAN MODOINDING KABUPATEN MINAHASA SELATAN (Contribution of Onion Farming to Family Income in Palelon Village Modoinding District, South Minahasa Regency) - Orlando Pendong; Sherly G. Jocom; Melsje Y. Memah (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
This study aims to determine the contribution of leek farming to family income in Palelon Village, Modoinding District, South Minahasa Regency. This research was conducted from December 2019 to February 2020. The data used came from primary data and secondary data and then analyzed descriptively. The results showed that the amount of income received by leek farmers in Palelon Village, Modoinding District was IDR 3,308,561 per farmer and IDR 4,726,516 per hectare. Contribution to family income was 86.48%. Based on these results, it could be concluded that the contribution of leek farming to family income was very high.